Exploring chiral interaction in hybrid materials and structures - Teh, Bing Hong (2015)
Chirality, the handedness of a matter, is all around us and is of great importance to us as biomolecules are all chiral due to tetrahedral bonding of at least one chiral carbon centre to four other different constituent groups of atoms in complex biomolecules. Enantiomer (opposite handedness) of a chiral molecule can either be ineffective (not broken down/absorbed) or even cause adverse side effect (Thalidomide) when consumed. [20] Hence, there is a need to be able to efficiently and accurately determine the chirality of the chiral molecules. Evanescent chiral electric field generated from scattering about a chiral nanostructures was found to significantly enhance sensitivity of adsorbed molecules to chiroptical effects and measurements. [21, 22] This report proposes a novel planar chiral design that is made up of entirely of nanoholes – Equilaterally Spaced with Overlap (ESO). A strong transmittance difference between right circularly polarized light and left circularly polarized light of 15% is obtained in simulation, corresponding to a CD in terms of degrees of 10°. Future work may venture into realizing the design and putting it to experiment with chiral molecules solution with the processes discussed in section 4 and section 6 in this report.